STRATEGI PENGEMBANGAN EKOWISATA MANGROVE DI TAMAN WISATA ALAM TELUK YOUTEFA KOTA JAYAPURA - Salusu, Fransisca Rimbunita (LPPM Universitas Nusa Mandiri, 2023)
Ecotourism is an alternative and sustainable tourism activity. What distinguishes ecotourism from other types of tourism is that ecotourism itself applies tourism activities with nature as the main object that must be managed with a great sense of responsibility, prioritizing aspects of empowering local communities, aspects of nature conservation and paying attention to educational elements. Based on the Decree of the Minister of Forestry of the Republic of Indonesia Number: 714/Kpts-II/1996, regarding the Designation of the Youtefa Bay Area as a Conservation Area Designated as a Natural Tourism Park with an area of 1,675 hectares. Not only is it rich in natural tourism, but with the existence of three villages in the Youtefa Bay Natural Tourism Park area, this area has cultural tourism and alternative religious tourism that can be an option for visiting tourists. However, inadequate facilities and infrastructure have made this Nature Tourism Park (TWA) area not often the choice of Jayapura City residents for sightseeing. This study aims to determine strategies that can be used in developing ecotourism in mangrove areas and improving the welfare of local communities. The method is carried out through a qualitative approach with primary and secondary data types and using a SWOT matrix analysis. From these methods generate strategies that can be used to develop TWA Teluk Youtefa including: tourism product development strategies (attractions, amenities, accessibility, ancillary), marketing development strategy and community involvement development strategy.